PROS HEBRAIOUS: THE EPISTLE TO THE HEBREWS AND ITS RELATIONSHIP TO SECOND TEMPLE JUDAISM - Strickland, Phillip David (My University, 2019)
The relationship between the Epistle to the Hebrews and Second Temple Judaism has long been a subject of debate within biblical scholarship. For most of the history of New Testament interpretation, Hebrews has been understood to be a Christian text written for the purpose of deterring Christians from relapsing back into their former religion, Judaism. Recently, however, scholars have argued for a variety of alternative proposals, and some have attempted to situate Hebrews as a text within Judaism. Consensus regarding Hebrews’s relationship to Judaism remains elusive, however, suggesting that a different way of approaching this issue is necessary. This dissertation argues that Hebrews is best understood as addressing the pastoral needs of a Jewish-Christian community facing a crisis related to issues of Jewish socioreligious identity. Using frameworks of social-historical description, theories of Jewish identity, and thematic analysis assisted by semantic domain theory, this research assesses Hebrews’s relationship to Judaism by examining the author’s treatment of themes related to the Law, the Temple, and the Promised Land, cultural frameworks which were significant for Jewish social and religious identity in the first century CE. This research finds that the writer of Hebrews textually constructs for himself and his audience an unmistakably Jewish identity. However, it will also be demonstrated that Hebrews evinces patterns of, as Steve Moyise says, ‘"both tradition and innovation” in how the writer appropriates vital identity-forming traditions from Judaism for his own pastoral purposes. This study, therefore, further contends that Hebrews evinces a community with an emerging Jewish-Christian identity as theirs is an expression of Judaism which has become largely defined by their devotion to Jesus. The context of looming crisis which permeates Hebrews and the writer’s treatment of traditions from common Judaism further suggests this community also has likely become estranged from Jerusalem and its temple system. This research thus contends that the traditional ‘‘relapse theory” interpretation which historically has interpreted Hebrews as taking a polemical stance against Judaism is without adequate support. Conversely, this research also suggests that some of the various “within Judaism” approaches which have become more popular in recent New Testament scholarship, while promising, require further nuancing when applied to Hebrews.
Keywords: Second Temple Judaism; Jewish socio-religious identity; Jewish identity